2022
DOI: 10.24875/aidsrev.22000001
|View full text |Cite
|
Sign up to set email alerts
|

Oral antivirals for the prevention and treatment of SARS-CoV-2 infection

Abstract: Vaccines and antivirals are the classical weapons deployed to contain, prevent, and treat life-threatening viral illnesses. Specifically, for SARS-CoV-2 infection, vaccines protect against severe COVID-19 disease manifestations and complications. However, waning immunity and emergence of vaccine escape mutants remains a growing threat. This is highlighted by the current surge of the omicron COVID-19 variant. Thus, there is a race to find treatment alternatives. We contend that oral small molecule antivirals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Secondly, our results could potentially be biased considering clinical contraindications by drug-drug interactions for nirmatrelvir/ritonavir, or patient preferences to avoid molnupiravir due to concerns about possible mutagenicity on fertility or pregnancy. 43 However, our analysis excluded patients with drug contraindications to nirmatrelvir/ritonavir, and those with severe renal or liver diseases for fair comparisons between oral antiviral users and matched controls. Thirdly, since the Ct value was no longer adopted as one of the discharge criteria during our study period, patients might have already been deemed clinically stable for discharge before reaching the specific cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our results could potentially be biased considering clinical contraindications by drug-drug interactions for nirmatrelvir/ritonavir, or patient preferences to avoid molnupiravir due to concerns about possible mutagenicity on fertility or pregnancy. 43 However, our analysis excluded patients with drug contraindications to nirmatrelvir/ritonavir, and those with severe renal or liver diseases for fair comparisons between oral antiviral users and matched controls. Thirdly, since the Ct value was no longer adopted as one of the discharge criteria during our study period, patients might have already been deemed clinically stable for discharge before reaching the specific cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Molnupiravir, a potent RNA-dependent RNA polymerase inhibitor, is the first approved oral antiviral agent for treating COVID-19. Ritonavir in combination with PF-07321332 was approved for emergency use by the US Food and Drug Administration on 22 December 2021 for the treatment of mild-to-moderate COVID-19 disease [ 2 ]. However, the severity of the ongoing global pandemic still urges the efforts to discover new antiviral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines and antivirals protect the people against severe COVID‐19 disease manifestations and complications. In this context, the emergency use of two antivirals, namely, molnupiravir and nirmatrelvir, has been approved, which may reduce disease progression by 30% and 89%, respectively, with 5 days use (Soriano et al, 2022 ). The commonly used drugs, their mechanism of action, and clinical trial results are also reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A number of repurposing drugs and steroids are commonly used to treat the disease. However, some serious side effects are observed as listed in (Soriano et al, 2022). The commonly used drugs, their mechanism of action, and clinical trial results are also reported in Table 1.…”
Section: Covid-19drugsmentioning
confidence: 99%